2006
DOI: 10.1080/10641950600745475
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin Concentration Prior to Clinical Onset of Preeclampsia

Abstract: Using this design, total adiponectin appeared not be a useful pre-clinical marker of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In our study, although pre-eclamptic women showed a slightly lower adiponectin than the control group, we did not observe any statistically significant difference in serum adiponectin between cases and controls both in univariate analysis and after adjustment for possible confounders. This finding is in accordance with two previous smaller studies showing no change in adiponectin values [2930]. But controversial data exist in the literature regarding adiponectin as predictive marker of PE.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, although pre-eclamptic women showed a slightly lower adiponectin than the control group, we did not observe any statistically significant difference in serum adiponectin between cases and controls both in univariate analysis and after adjustment for possible confounders. This finding is in accordance with two previous smaller studies showing no change in adiponectin values [2930]. But controversial data exist in the literature regarding adiponectin as predictive marker of PE.…”
Section: Discussionsupporting
confidence: 93%
“…However, only one of such previous studies distinguished between early and late PE and reported that the levels of adiponectin were increased only in late PE [25] . Three previous studies examined firsttrimester maternal levels in women who subsequently developed PE and 1 reported no significant differences in adiponectin levels between cases and controls [10] , whereas 2 studies demonstrated that in the PE group the levels were decreased [9,26] . One of the studies examined differences between early and late PE and reported that significant reduction in plasma adiponectin was observed only in the cases that developed late PE [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Maternal factorderived a priori risks for PE were determined as previously described and were then logarithmically transformed [17] . Logistic regression analysis was used to determine if the log-transformed maternal factor-derived a priori risks, sqrt adiponectin MoM, log 10 The statistical software package SPSS 16.0 (SPSS Inc., Chicago, Ill., USA) was used for data analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence concerning maternal adiponectin concentrations in the presence of preeclampsia is inconsistent: higher [41, 58, 59, 70, 92, 112, 113, 116, 130, 159], lower [31, 33, 34, 63, 125], and similar adiponectin concentrations [119, 120, 145, 160] have been reported in patients with preeclampsia compared to normal pregnant women. This alleged inconsistency may be due to differences in the study population characteristics, definitions of preeclampsia (mild vs. severe, early vs. late onset), sample size or methods by which adiponectin concentrations were determined.…”
Section: Discussionmentioning
confidence: 99%